2010
DOI: 10.1002/ceat.200900622
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Oxidized Sulfur‐Containing Compounds of Non‐Hydrotreated Gas Oil

Abstract: The desulfurization of non-hydrotreated gas oil using oxidation followed by liquid/liquid extraction has been studied. The solvent extraction of oxidized sulfur-containing compounds of gas oil was carried out by utilizing various types of solvents, including acetonitrile, methanol, and 96 vol.-% ethanol. The performance of these solvents was carefully evaluated and compared by considering both desulfurization and gas oil recovery. It was found that their performance follows the order: acetonitrile > methanol >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…M a n u s c r i p t Table 2 The physical properties and desulfurization rate of diesel of these solvents. a Solvent properties from: [13] b Hildebrand values from: [20] A c c e p t e d M a n u s c r i p t 13 Table 3 Effect of binary-solvent on the EDS reaction in diesel. M a n u s c r i p t 14 Table 5 Physicochemical properties of the commercial diesel, treated diesel and Euro IV standard.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…M a n u s c r i p t Table 2 The physical properties and desulfurization rate of diesel of these solvents. a Solvent properties from: [13] b Hildebrand values from: [20] A c c e p t e d M a n u s c r i p t 13 Table 3 Effect of binary-solvent on the EDS reaction in diesel. M a n u s c r i p t 14 Table 5 Physicochemical properties of the commercial diesel, treated diesel and Euro IV standard.…”
Section: Discussionmentioning
confidence: 99%
“…It is also desirable for the solvent to have a large difference in density and boiling point in the separation of organosulfur compounds [13]. However, in this study although NMP and DMSO each showed a high extractability for sulfur, their boiling points were rather close to the boiling points of organosulfur compounds.…”
Section: The Potentially Effective Solvent For S Removalmentioning
confidence: 92%
See 1 more Smart Citation
“…The number of extraction steps can play a significant role in the removal of the oxidized sulfur compounds during the extraction of waste tire oil. It is expected that the desulfurization efficiency will be increased upon increasing the number of extraction steps in order to improve the extraction efficiency of the oxidized sulfur compounds [42]. In this study, the extraction of the oxidized sulfur compounds was investigated using acetonitrile as the extracting solvent.…”
Section: The Effect Of the Number Of Extraction Steps On The Desulfurmentioning
confidence: 99%
“…After oxidation, the real oil samples were extracted in two steps, 1 st step extraction with 80% acetonitrile, and second step extraction with 80% methanol. Initial experiments revealed that single step extraction was insufficient for complete removal of the oxidized sulfur compounds from real oil samples, since the 80% acetonitrile extraction was found effective for oxidized gas oil [30], hence 2 stage extraction was used. The oil samples used as feed were untreated naphtha (NP), It is also revealed from the results that during the catalytic ODS the sulfur removal gradually decreases in case of real oil samples as its density or boiling range increases i.e.…”
Section: Ods Of Real Oil Samplesmentioning
confidence: 99%